Characterization of diabetic osteoarthritic cartilage and role of high glucose environment on chondrocyte activation: toward pathophysiological delineation of diabetes mellitus-related osteoarthritis. Issue 9 (September 2015) - Laiguillon, M.-C.; Courties, A.; Houard, X.; Auclair, M.; Sautet, A.; Capeau, J.; Fève, B.; Berenbaum, F.; Sellam, J.
Summary: Objective: To examine the relationship between osteoarthritis (OA) and type 2 diabetes mellitus (DM). Methods: OA cartilage from DM and non-DM patients undergoing knee replacement were stimulated by IL-1β for 24 h and release of interleukin-6 (IL-6) and prostaglandin E2 (PGE2 ) was measured. Primary cultured murine chondrocytes were stimulated for 24 and 72 h with or without IL-1β (5 ng/mL) under normal-glucose (5.5 mM) or high-glucose (25 mM) conditions. The expression and release of pro-inflammatory mediators (IL-6, cyclooxygenase 2 [COX2]/PGE2 ) were analyzed by quantitative RT-PCR and ELISA/EIA. Glucose uptake was assessed with ( 14 C)-2-deoxyglucose. Reactive oxygen species (ROS) and nitric oxide (NO) production were measured. To analyze the mechanism of IL-1β-induced inflammation, cells were pretreated or treated with inhibitors of glucose transport (cytochalasin B), the polyol pathway (epalrestat), mitochondrial oxidative stress (MitoTEMPO) or nitric oxide synthase (l -NAME). Results: With IL-1β stimulation, IL-6 and PGE2 release was greater in human DM than non-DM OA cartilage (2.7- and 3-fold, respectively) ( P < 0.05). In vitro, with IL-1β stimulation, IL-6 and COX2 mRNA expression, IL-6 and PGE2 release, and ROS and NO production were greater under high-than normal-glucose conditions in cultured chondrocytes. IL-1β–increased IL-6 release was reduced with cytochalasin B, epalrestat, l -NAME or MitoTEMPO treatment (−45%, −62%, −38% and −40%, respectively). Conclusion: OA cartilages from DM patients showed increased responsiveness to IL-1β–induced inflammation. Accordingly, high glucose enhanced IL-1β–induced inflammation in cultured chondrocytes via oxidative stress and the polyol pathway. High glucose and diabetes may thus participate in the increased inflammation in OA.